Utilization of Youtube as a Problem Solving-Based Learning Media - Kurniawan, Andri; Pattiasina, Petrus Jacob; Rahman, Arief; Lestari, Nana Citrawati; Haddar, Gamar Al (PT.KARYA GEMAH RIPAH, 2024)
Education in the digital age demands innovative approaches to learning, particularly in developing problem-solving skills. The main problem faced in traditional education is the lack of real context and practical situations that stimulate students' critical and creative thinking. A potential solution to this problem is the utilization of YouTube as a problem-solving-based learning medium. YouTube provides access to a variety of educational content featuring case studies, simulations, and real-life examples, which can assist students in understanding and applying concepts in a more practical context. This study uses mixed research methods to investigate how YouTube can be utilized in problem-solving-based learning. Data collection was conducted through quantitative surveys and qualitative interviews with students and educators who have used YouTube in their learning. Data analysis shows that the integration of YouTube in learning can improve students' concept understanding, facilitate problem identification and analysis, and support the real-time exchange of ideas and solutions through the interactivity of the platform. The results show the potential of YouTube as an innovative learning tool that can improve students' problem-solving skills. The use of educational videos and interactive features such as comments and live streaming encourage student engagement and collaborative learning. This research provides insights for educators in designing and implementing learning strategies that utilize digital technology effectively.